Postprocedural morphology change of non-covalent nanoparticle-polymer hybrids from silica and self-assembled polystyrene-block-polyacrylic acid vesicles - Jil Mann; Sherif Okeil; Georg Garnweitner; Carsten Schilde (Nanocomposites)
Self-assembled non-covalent nanoparticle-polymer hybrids, that can combine a variety of desired properties in a single material with highly dynamic structure, have great potential in the field of functional nanosystems. In this study, we present a method for preparing such hybrids from silica nanoparticles and polymer structures of polystyrene-block-polyacrylic acid (PS-b-PAA). We show that the surface chemistry of the nanoparticles has a major influence on the encapsulation efficiency and the localization of the particles in the vesicles. Furthermore, an increase in vesicle size was observed with higher vesicle loading. A particular highlight of this work is that the morphology of the hybrids could be subsequently modified by adjusting the solvent composition. It was also found that the presence of the particles led to faster transitions due to the increased free energy of the system. This type of morphological change therefore offers promising potential applications, such as self-healing materials.